PENGARUH PROFITABILITAS, LIKUIDITAS, UKURAN PERUSAHAAN DAN BETA TERHADAP RETURN SAHAM DI PERUSAHAAN YANG TERGABUNG DALAM INDEKS LQ 45 - Andini Permana Sari, Sila; Damayanti, Damayanti (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
Many people in Indonesia have a lot money and choose to invest in capital growing activities in the hope of gaining a profit in the future. Therefore, the purpose of this study is to demonstrate how the return on shares of firms listed on the Indonesian Stock Exchange that are included in the LQ 45 Index is affected by factors such as profitability, liquidity, company size, and systematic risk. The population of this study included companies listed on LQ 45 of the Indonesia Stock Exchange from 2018 to 2022. The sample used in the study consisted of 13 companies. Sampling techniques with targeted sampling. Double linear regression analysis is used as the data analysis technique. The results of this study show that a company’s profitability, liquidity, and size do not have a significant negative impact on stock returns and systematic risk had no major positive impact on the return company shares incorporated into the Indonesian Stock Exchange’s LQ 45 indicator. Adjusted R2 is 0,016. It can than be understood that the 1,6% variation in the price to earnings ratio percentage of companies listed on the LQ 45 index of the Indonesia Stock Exchange can be accounted for by the four independent variabels: systematic risk, profitability, liquidity, and company size. On the other hand, other variabels not covered in this study are used to describe the remaining 98,4%.